2017
DOI: 10.1016/j.juro.2016.11.054
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-Term Followup of Proximal Hypospadias Repair Reveals High Complication Rate

Abstract: Purpose Results following distal hypospadias repair are favorable. Grouping proximal and distal hypospadias repair artificially increases the perceived success rate of proximal hypospadias. We identified our complication rate of proximal hypospadias repair and hypothesized a higher complication rate for 1-stage repair. Materials and Methods We retrospectively reviewed the records of consecutive boys who underwent proximal hypospadias from 2007 to 2014. Proximal hypospadias was defined as a urethral meatus lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 26 publications
(31 reference statements)
3
72
0
3
Order By: Relevance
“…24,25 The most recent studies from major centres have unanimously suggested that the failure rate of primary repair of proximal hypospadias has actually been underreported in the literature. 6,26,27 Our finding of increased odds of failure in primary repair of proximal hypospadias when compared with the distal type is in agreement with the current evidence. We did not find age at the time of surgery and surgical techniques to be independent predictors of repair failure, and our finding is in agreement with other studies.…”
Section: Discussionsupporting
confidence: 90%
“…24,25 The most recent studies from major centres have unanimously suggested that the failure rate of primary repair of proximal hypospadias has actually been underreported in the literature. 6,26,27 Our finding of increased odds of failure in primary repair of proximal hypospadias when compared with the distal type is in agreement with the current evidence. We did not find age at the time of surgery and surgical techniques to be independent predictors of repair failure, and our finding is in agreement with other studies.…”
Section: Discussionsupporting
confidence: 90%
“…50,51 A systematic review comparing TIP to onlay preputial flaps for proximal hypospadias without significant VC showed no significant difference in urethroplasty complication rates. 52 The Koyanagi repair has shown favourable results for proximal hypospadias, with a 17% complication rate in a series of 151 proximal hypospadias children.…”
Section: Proximal Hypospadiasmentioning
confidence: 99%
“…Dorsal penile plication and urethral plate elevation (mobilization) are two maneuvers that have been described to correct chordee while preserving the urethral plate for urethroplasty [6] ; however, recurrence of chordee remains a major concern that seems to be under-reported in the literature [2,16,17] . Moreover, exaggeration of penile chordee may be expected as the child goes into puberty [3,7,10] . Therefore, the threshold for sacrificing the urethral plate has been lowered in most recent reports [2,18] ; only mild ventral curvature (<300) would be suitable for techniques that preserve the urethral plate [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Observing the child during micturition and measuring residual urine volume by ultrasound were very helpful and reassuring for both parents and doctors; urethrograms, cystoscopy, and flow-metery can be of value in selected cases. Cases that return for reoperation (fistula, chordee, skin refashioning) represent an excellent opportunity to evaluate the neourethra under anesthesia (endoscopy/calibration) [10] ; this group represented 21% of our cases. In our practice, we report a very low incidence of urethral strictures (0.5%) following TIP urethroplasty (only one case that showed good response to dilatation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation